Analysis of the Implementation of Interactive Media as a Learning Support at Al-Azhar Flagship High School Medan: Penelitian - Aulya Aprilyani; Azqy Amanatun Syahrani Purba; Aura Adni Audia; Athar Fattah Fawwaz Syah; Alya Ramadhani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the implementation of interactive media as a learning support in Al-Azhar Superior High School Medan. The research background departs from the increasing need for learning media that is varied and adaptive to the characteristics of students of the digital generation. Interactive media is believed to be able to increase learning engagement and effectiveness, as shown by various previous studies. This study used a quantitative descriptive method involving 36 students in grade XII UG E as a sample. The research instrument is in the form of a Likert scale questionnaire that has been validated through expert judgment and tested for reliability using Cronbach Alpha. The data was analyzed using descriptive statistics in the form of percentages, averages, and frequency distributions. The results of the study show that students have a strong preference for learning media that are active and visual. Game-based media is the most popular choice with a percentage of 30.6%, followed by video learning at 27.1%. Interactive quizzes take the next position, while PowerPoint and discussion forums gain moderate interest. The media with the lowest level of interest are the teacher's explanations directly as well as entertainment platforms such as Netflix/Disney. These findings suggest that students are more interested in media that provide a hands-on, interactive, and fun learning experience.